Autoregulatory Feedback Mechanism of P38MAPK/Caspase-8 in Photodynamic Therapy-Hydrophilic/Lipophilic Tetra-α-(4-carboxyphenoxy) Phthalocyanine Zinc-Induced Apoptosis of Human Hepatocellular Carcinoma Bel-7402 Cells - Yu Wang; Chunhui Xia; Wei Chen; Yuhang Chen; Yiyi Wang; Tao Li (International Journal of Photoenergy)
Photodynamic therapy (PDT) is a novel and promising antitumor treatment. Our previous study showed that hydrophilic/lipophilic tetra-α-(4-carboxyphenoxy) phthalocyanine zinc- (TαPcZn-) mediated PDT (TαPcZn-PDT) inhibits the proliferation of human hepatocellular carcinoma Bel-7402 cells by triggering apoptosis and arresting cell cycle. However, mechanisms of TαPcZn-PDT-induced apoptosis of Bel-7402 cells have not been fully clarified. In the present study, therefore, effect of TαPcZn-PDT on apoptosis, P38MAPK, p-P38MAPK, Caspase-8, Caspase-3, Bcl-2, Bid, Cytochrome c, and mitochondria membrane potential in Bel-7402 cells without or with P38MAPK inhibitor SB203580 or Caspase-8 inhibitor Ac-IEFD-CHO was investigated by haematoxylin and eosin (HE) staining assay, flow cytometry analysis of annexin V-FITC/propidium iodide (PI) double staining cells and 5,5′,6,6′-tetrachloro-1,1′,3,3′-tetraethylbenzimidazolylcarbocyanine iodide (JC-1), and immunoblot assay. We found that TαPcZn-PDT resulted in apoptosis induction, activation of P38MAPK, Caspase-8, Caspase-3, and Bid, downregulation of Bcl-2, release of Cytochrome c from mitochondria, and disruption of mitochondrial membrane potential in TαPcZn-PDT-treated Bel-7402 cells. In contrast, SB203580 or Ac-IEFD-CHO attenuated induction of apoptosis, activation of P38MAPK, Caspase-8, Caspase-3, and Bid, downregulation of Bcl-2, release of Cytochrome c from mitochondria, and disruption of mitochondrial membrane potential in TαPcZn-PDT-treated Bel-7402 cells. Taken together, we conclude that Caspase-3, Bcl-2, Bid, and mitochondria are involved in autoregulatory feedback of P38MAPK/Caspase-8 during TαPcZn-PDT-induced apoptosis of Bel-7402 cells.